Efficacy of sunscreen with photolyase or regular sunscreen associated with topical antioxidants in treating advanced photodamage and cutaneous field cancerization: a randomized clinical trial - Alvares, Bruno Augusto [UNESP]; Miola, Anna Carolina [UNESP]; Schimitt, Juliano Vilaverde [UNESP]; Miot, Helio Amante [UNESP]; Abbade, Luciana Patricia Fernandes [UNESP] (Elsevier, 2022)
Background: Several treatments are available for skin with advanced photodamage, which is characterized by the presence of actinic keratoses (AK). Objectives: Evaluate the efficacy of using sunscreen with photolyase compared to regular sunscreen, as well as to compare the combination of a topical formulation of antioxidants versus placebo in the treatment of advanced photodamage. Methods: This was a randomized, double-blind, factorial clinical trial. Participants with AKs on their forearms were randomized to apply regular sunscreen (SC) or sunscreen with photolyase (SC+P) on both forearms during the day. One of the forearms in each group was randomized again to receive topical antioxidants (AOx), and the other forearm received a placebo cream (both for night application). The four groups were SC/AOx, SC/placebo, SC+P/AOx, and SC+P/placebo. The duration of treatment was 8 weeks. Primary outcomes were total AK clearance, decrease in Forearm Photoaging Scale (FPS), and AK severity scores. Secondary outcomes were reduction in AK count, partial clearance rate, and safety. Results: Forty participants (80 forearms) were included. All groups showed significant improvement in outcomes at week eight. There were no significant differences between SC and SC+P for either outcome. AOx led to a significant reduction in AK count (22%; p < 0.05). Partial clearance was obtained in 18 (47.4%) forearms treated with AOx and in 9 (23.7%) treated with placebo (p < 0.05). All groups reduced the FPS score, without significant differences among them. Conclusions: There is no difference in the treatment of advanced photodamage skin when comparing the use of sunscreen with photolyase and regular sunscreen, and topical antioxidants were more efficient in reducing AK count than placebo. Study limitations: Short interval of follow-up and absence of re-evaluation in the absence of treatment were limitations of the present study.
Keywords: Actinic keratosis; Antioxidants; Deoxyribodipyrimidine photo-lyase; Skin aging; Skin neoplasms; Sunscreening agents